2016
DOI: 10.1126/science.aad9279
|View full text |Cite
|
Sign up to set email alerts
|

Parasites resistant to the antimalarial atovaquone fail to transmit by mosquitoes

Abstract: Drug resistance compromises control of malaria. Here, we show that resistance to a commonly used antimalarial medication, atovaquone, is apparently unable to spread. Atovaquone pressure selects parasites with mutations in cytochrome b, a respiratory protein with low but essential activity in the mammalian blood phase of the parasite life cycle. Resistance mutations rescue parasites from the drug but later prove lethal in the mosquito phase, where parasites require full respiration. Unable to respire efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 41 publications
2
130
1
Order By: Relevance
“…More recently, a study has shown that atovaquone resistance cannot be transmitted via mosquitoes (23). This study reported that atovaquone drug pressure selects for the M133I cytb mutation in P. berghei, which is consistent with our data on menoctone drug pressure.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…More recently, a study has shown that atovaquone resistance cannot be transmitted via mosquitoes (23). This study reported that atovaquone drug pressure selects for the M133I cytb mutation in P. berghei, which is consistent with our data on menoctone drug pressure.…”
Section: Discussionsupporting
confidence: 82%
“…We conclude that menoctone-and atovaquone-resistant parasites containing the M133I mutation in cytb are indeed transmittable by the mosquito vector. At present, we do not understand why P. berghei with M133I mutations were transmitted in our study but not in the recent study by Goodman et al (23). The difference could be due to inherent transmissibility of the different P. berghei strains or mosquitoes used in the respective studies.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Because both ATV and ELQ-300 act on a single protein, the development of simultaneous Q o and Q i site mutations would be exceedingly rare, and the fact that the mitochondrial genome is carried in only female gametocytes would prevent any dual-site resistance secondary to genetic recombination at the sexual stage. Even if rare ATV r /ELQ-300 r mutants were to arise, recent work suggests that these parasites would likely be incapable of transmission by mosquitoes; the McFadden group has recently shown that multiple ATV r mutations (including Y268C and Y268N) are associated with arrested oocyst development within the mosquito midgut and with a failure to produce the infectious sporozoites necessary for transmission to mammalian hosts (26). Ultimately, we believe that ATV and ELQ-300 could be ideal partner drugs with a low propensity for drug resistance and with the remarkable potency characteristic of cyt bc 1 inhibitors.…”
mentioning
confidence: 99%
“…RIcT and RIaT therefore could be developed as useful tools to predict the potential emergence of resistance to antimalarials. In the case of atovaquone, the rapid within-host selection of resistance had not been followed by its spread in the population, presumably because parasites that are resistant to atovaquone are not transmissible by mosquitoes due to the resulting defective sexual cycle (12). However, information regarding the potential emergence of resistance to other antimalarials currently used, as well as newly introduced compounds, could provide knowledge essential for planning malaria control and devising strategies to delay the emergence of resistance.…”
Section: Dose-dependent Selection Of Atovaquone Resistance Antimicrobmentioning
confidence: 99%